Efeito da alimentação suplementar sobre o tamanho populacional estimado e os caracteres morfológicos de adultos de Melipona seminigra merrillae Cockerell, 1919 (Apidae, Meliponini) - Campelo, Janaina da Cruz (Entomologia, 2024)
The food resources of bees (nectar and pollen) are subject to large fluctuations throughout the year due to the reproductive cycle of plants, seasons, etc., and therefore may not always be available in sufficient quantity and quality. Furthermore, in the practice of meliponiculture, the availability of these resources may be reduced because of the clustering of several colonies in a single location. Momentary scarcity of food in nature can cause a decrease or pause in egg laying by the queen, weakening and, even leading the colony to death. During periods of temporary food scarcity, supplemental feeding is necessary to ensure that the colonies remain in good condition until the next flowering season. However, little is known about the effects of this supplementation on colonies and their individuals. This study comparatively evaluated the effect of supplemental feeding on the estimated population size and morphological characteristics of adult workers in a colony of Melipona seminigra merrillae Cockerell, 1919 maintained in a meliponary. We used colonies from two urban meliponaries in Manaus (GPA-INPA scientific meliponary and Alvorecer meliponary) that, over a period of 21 weeks (August 2021 to January 2022), were supplemented weekly with the following feedings: T1—Syrup (Control), T2—Pollen, T3—Soy, and T4—Aminomix, in addition to free access to meliponicultural pasture. The population size was estimated by the number of sealed brood cells weekly and by the number of bees leaving the colony in a 5-minute period, counted before (zero time) and at different times (70, 95, 120, and 145 days) after the start of feedings. Morphometric analysis provided data on interocular distance, intertegular distance, corbicular area, wing size, and fluctuating asymmetry (FA) of wing shape at different times (0, 70, 95, 120, and 145 days of supplemental feeding). To evaluate the effect of feedings on population size and morphological characteristics of bees over time and in different meliponaries, we used different Generalized Linear Mixed Models (GLMMs) that were subjected to Analysis of Variance (ANOVA) and, when possible, Tukey's multiple comparisons. At the end of the experimental period, it was observed that the mean number of brood cells for the colonies among treatments was as follows: T1—Syrup with 5,779 cells, T2—Pollen with 5,614 cells, T4—Aminomix with 5,162.3 cells, and T3—Soy with 4,541 brood cells. However, supplemental feedings did not have a significant effect on population size over time and in the two meliponaries. Through analysis of morphological characteristics, it was found that feedings T2—Pollen, T3—Soy, and T4—Aminomix did not affect the body size and symmetry of wing shape of workers over time. However, when evaluating the effect of feedings on body size of workers, considering each meliponary, different results were observed. While in GPA-INPA feeding T4 reduced the interocular distance over time, in Alvorecer, bees fed with T2 had the smallest intertegular distance. Variations in the composition of feedings, as well as environmental differences around each meliponary, certainly contributed to the observed effects. Therefore, we consider it economically more interesting for meliponicultors to use only syrup in their colonies compared to other feedings analyzed in this study.
Keywords: Abelhas "sem-ferrao"; Suplementação alimentar; Morfometria